Clinicians' Perceptions of the Benefits and Harms of Prostate and Colorectal Cancer Screening. (May 2015) - Elstad, Emily A.; Sutkowi-Hemstreet, Anne; Sheridan, Stacey L.; Vu, Maihan; Harris, Russell; Reyna, Valerie F.; Rini, Christine; Earp, Jo Anne; Brewer, Noel T.
Background. Clinicians' perceptions of screening benefits and harms influence their recommendations, which in turn shape patients' screening decisions. We sought to understand clinicians' perceptions of the benefits and harms of cancer screening by comparing 2 screening tests that differ in their balance of potential benefits to harms: colonoscopy, which results in net benefit for many adults, and prostate-specific antigen (PSA) testing, which may do more harm than good. Methods. In this cross-sectional study, 126 clinicians at 24 family/internal medicine practices completed surveys in which they listed and rated the magnitude of colonoscopy and PSA testing benefits and harms for a hypothetical 70-year-old male patient and then estimated the likelihood that these tests would cause harm and lengthen the life of 100 similar men in the next 10 years. We tested the hypothesis that the availability heuristic would explain the association of screening test to perceived likelihood of benefit/harm and a competing hypothesis that clinicians' gist of screening tests as good or bad would mediate this association. Results. Clinicians perceived PSA testing to have a greater likelihood of harm and a lower likelihood of lengthening life relative to colonoscopy. Consistent with our gist hypothesis, these associations were mediated by clinicians' gist of screening (balance of perceived benefits to perceived harms). Limitations. Generalizability beyond academic clinicians remains to be established. Conclusions. Targeting clinicians' gist of screening, for example through graphical displays that allow clinicians to make gist-based relative magnitude comparisons, may influence their risk perception and possibly reduce overrecommendation of screening.